Applying a gender lens to social norms, couple communication and decision making to increase modern contraceptive use in Ethiopia, a mixed methods study - Nandita Kapadia-Kundu; Habtamu Tamene; Minyahil Ayele; Feleke Dana; Simon Heliso; Sanjanthi Velu; Tsega Berhanu; Guda Alemayehu; Lindsey Leslie; Michelle Kaufman (BMC, 2022)
Plain Language summary A reproductive health study involving mixed quantitative and qualitative methods was conducted in Ethiopia in 2016-2017. The overall objectives of the study are (1) to use mixed methods research to identify determinants of contraceptive use in four regions of Ethiopia, and (2) to explore the relationship between social norms, gender equitable norms, couple communication, and contraceptive use. The survey identified gender inequitable norms as a major barrier to contraceptive use. The qualitative study further examined the gender dimension and the interlinkages between gender norms, couple communication, and decision making for contraceptive use. Data showed that gender norms related to the daily living dimension of the gender equitable men (GEM) scale are significantly associated with current contraceptive use. The qualitative component provides us with in-depth data on the daily experiences of rural Ethiopian women in the context of modern contraceptive use. We learned that social norms related to the desired number of children and the timing of first contraceptive use are interlinked. Specifically, both women and men told us that most couples do not use contraceptives until their family size is complete, after 4-5 children. Similarly, couples who opt for 2 or fewer children are termed "selfish" and "not interested in children." Couple communication occurs within the context of decision making where men's decisions are usually accepted, and women's decisions are often deferred or rejected. Programs should promote respect for women's decision-making abilities and equitable couple communication. Notably, this study finds that microprocesses of couple communication and decision making are gendered, featuring female disadvantage. Further research is required on these microprocesses of gendered couple communication.